UMPSA engages with UMPSA-BJTU dual degree students undergoing industrial training at Liuzhou Railway Technical and Vocational College, China - Abd Razak, Ja'afar (UMPSA, 2025)
LIUZHOU, CHINA, 11 June 2025 – Students of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) who are currently enrolled in the UMPSA–Beijing Jiaotong University (BJTU) dual-degree programmes were thrilled to meet with representatives of the university’s management recently in Liuzhou, China.